2010
DOI: 10.1038/emboj.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

AGAP1/AP-3-dependent endocytic recycling of M5 muscarinic receptors promotes dopamine release

Abstract: Of the five mammalian muscarinic acetylcholine (ACh) receptors, M(5) is the only subtype expressed in midbrain dopaminergic neurons, where it functions to potentiate dopamine release. We have identified a direct physical interaction between M(5) and the AP-3 adaptor complex regulator AGAP1. This interaction was specific with regard to muscarinic receptor (MR) and AGAP subtypes, and mediated the binding of AP-3 to M(5). Interaction with AGAP1 and activity of AP-3 were required for the endocytic recycling of M(5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 77 publications
(124 reference statements)
6
61
1
Order By: Relevance
“…Earlier studies show that muscarinic agonists potentiate DA efflux in the striatum (5)(6)(7)(8). However, other studies reported that mAChR agonists depress DA transients measured with fast-scan cyclic voltammetry (FSCV) and evoked by electrical stimulation in the striatum (9)(10)(11). Thus, the role of mAChRs in modulating striatal DA transmission remains controversial and unclear.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier studies show that muscarinic agonists potentiate DA efflux in the striatum (5)(6)(7)(8). However, other studies reported that mAChR agonists depress DA transients measured with fast-scan cyclic voltammetry (FSCV) and evoked by electrical stimulation in the striatum (9)(10)(11). Thus, the role of mAChRs in modulating striatal DA transmission remains controversial and unclear.…”
mentioning
confidence: 92%
“…Although direct anatomic evidence for the presence of M 5 receptors in DA axons is lacking, functional studies implicate M 5 mAChRs in either facilitating (8,10) or depressing (11) DA release. In the past, studies in this field have been hampered by the lack of selective muscarinic agonists and antagonists (18).…”
mentioning
confidence: 99%
“…Future studies will determine if the interaction of ArfGAP1 with Arf1 and cargo affects vesicle formation and whether other ArfGAPs, such as ArfGAP2 and 3 and AGAPs, that bind to coat proteins and cargo 12,15,[69][70][71] function by a mechanism analogous to ArfGAP1.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…AGAP1 binds directly to the clathrin adaptor protein AP-3, which together with clathrin can form a vesicular coat (9). AGAP1 also binds to muscarinic receptor and affects its trafficking (10). The related protein AGAP2 binds to ␤-arrestin, which affects Erk signaling (11), and to focal adhesion kinase, which controls focal adhesions and, presumably, cell migration (12), a plausible function for AGAP1 as well given its effect on both actin cytoskeleton and membrane traffic (8).…”
mentioning
confidence: 99%